Pelestarian pengetahuan lokal melalui transfer pengetahuan di Rurukan Adat â€œNabawadatalaâ€ Sumedang - Waty, Windi Widia; Yusup, Pawit M.; Yanto, Andri (Berkala Ilmu Perpustakaan dan Informasi, 2020)
Introduction. The research aims to examine knowledge transfer by a local community Rurukan Adat "Nabawadatala" in preserving local knowledge ion Citengah village â€“ Sumedang, West Java. Data Collection Method. This research used qualitative approach with a case study method. Data Analysis. Qualitative data analysis was conducted iteratively and continuously until reach the data saturation. The three steps of data analysis were conducted, including data reduction, data display, and conclusion drawing/verification. Results and Discussion. Pattern transfer occurred in the study includes three processes, namely the preparation of sustainable work plan; the concept of learning and knowledge sharing; and the creation of knowledge to form a tourist area-based education. Conclusion. A cultural centre established by the Citengah village community leaders to support knowledge transfer is very useful, not only for people inside of the community, but also for people around the community.